Demand side management potential at the bharati hospital and research centre - Kripachariya Singh Sagolsem; Swati S More (Institute of Advanced Engineering and Science, 2012)
The present paper has the main aim of illustrating some main results obtained from a walk through preliminary energy audit performed on The Bharati Hospitals and Research centre, Pune, India. These results are analyzed in order to determine an optimum consumption pattern and potential of saving in terms of expenditure towards energy cost.DOI:http://dx.doi.org/10.11591/ijece.v2i4.480